The exercise of the right of prison inmates to have contact with their children in the context of contemporary research on childhood - Karolina Chorąży; Justyna Kusztal (Problemy Wczesnej Edukacji)
The article relates to the subject of the presence of adults in the world of children, because it presents the results of research conducted between December 2021 and April 2022, concerning the ways of exercising the right of prison inmates to have contact with their children. The research was conducted based on the method of a systematic review of literature, where the analysis was based on academic articles published in 3 journals, i.e. “Resocjalizacja Polska”, “Archiwum Kryminologii”, and “Nowa Kodyfikacja Prawa Karnego” from 2017 to 2021, and on legal acts. Many articles concluded that the relationships of imprisoned parents with their children have a major impact on the process of the parents’ social rehabilitation, because the parent-child bond is an important factor in this process.